Reading Elizabeth Bishop : an Edinburgh companion - Ellis, Jonathan, 1975- (Edinburgh companions to literature and the humanities., 2019)
This collection of essays offers a comprehensive and original guide to Elizabeth Bishop's poetry and other writing, including literary criticism and prose fiction. It celebrates Bishop as an international writer with allegiances to various countries and national traditions, including but not limited to the countries she lived in and felt at home. In doing so, it explores how Bishop moves between literal geographies like Nova Scotia, New England, Key West and Brazil, but also more slippery categories like home and elsewhere, human and animal, insider and outsider.